SINERGI MANAJEMEN MUTU HAFALAN DAN PEMASARAN PESANTREN DALAM MENUMBUHKAN MINAT SANTRI MENGHAFAL AL-QUR’AN - Muhammad Zidan Al-Azmy; Suwandi Suwandi (Jurnal Manajemen Pendidikan, 2026)
Objective: This study aims to analyze the influence of memorization quality management and marketing strategy on students’ interest in memorizing the Qur’an at Pondok Pesantren Safinatul Huda Jombang. The study focuses on examining both partial and simultaneous effects of the two independent variables on students’ interest in the tahfiz program. This research employed a quantitative approach with a survey method. Data were collected through questionnaires distributed to students participating in the Qur’an memorization program. The data were analyzed using IBM SPSS Version 27 through classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination. The findings show that memorization quality management has a positive and significant effect on students’ interest, with a t-value of 5.199. Marketing strategy also has a positive and significant effect, with a t-value of 2.333. Simultaneously, both variables significantly influence students’ interest, as indicated by an F-value of 34.579. The coefficient of determination shows that memorization quality management and marketing strategy contribute 49.0% to students’ interest, while the remaining 51.0% is influenced by other factors. This study offers a distinctive perspective by integrating internal quality management of Qur’an memorization with institutional marketing strategy as a combined framework for increasing students’ interest in tahfiz-based Islamic boarding schools.